EFFECT OF THE USE OF MULTIPLYING STRAINS WITH EFFICIENT MICROORGANISMS IN THE BIOREMEDIATION OF AQUACULTURE AND WASTEWATER FROM PRODUCTIVE FISH-FARMING LAKES - Olaya, Maria Angélica Beltrán; Gonzalez, Carlos Alberto Cervera; Arrieta, Diana Palacios (Seven Editora, 2025)
The intensification of aquaculture activity has increased the generation of organic waste and toxic compounds, such as nitrogen and phosphorus, threatening the quality of surface water bodies and environmental sustainability. This study aimed to evaluate the effectiveness of multiplying strains of efficient microorganisms (EM) in the bioremediation of culture water and wastewater from fish-farming lakes. The methodology consisted of physicochemical and microbiological characterization of the waters and the application of three experimental EM doses (1/110, 1/1000, and 1/3000) in 250-liter units, compared with a control over a 45-day period. The evaluated parameters included COD, total solids, nitrogen compounds (ammonium, nitrites, nitrates), phosphates, sulfates, and microbiological counts (coliforms and heterotrophs). The results showed that although there was an increase in dissolved oxygen over time, there were no statistically significant differences between the EM treatments and the control for most variables, including the removal of coliforms and nitrogen compounds. The exception was sulfate levels, for which a significant reduction was observed in the EM treatments. It was also observed that the highest dose (1/110) was counterproductive, inducing a eutrophication process and macrophyte growth that increased the organic matter and phosphate load. It is concluded that, under the studied conditions, EM were effective specifically for sulfate removal, and lower doses are recommended for future studies to avoid eutrophication. DOI: https://doi.org/10.56238/sevened2025.036-154